Spirituality-Driven Public Relations with The Panca Reputation Pesantren in Image Building - Najiburahman, Najiburahman; Khusnuridlo, Moh; Muhith, Abd; Imam, Ombra A (JURNAL AL-TANZIM, 2024)
This study aims to analyze the contribution of spirituality-based public relations management in building the image of Islamic boarding schools in society, based on Fombrun's perspective. This study is based on the importance of Islamic boarding schools as educational institutions that educate students and contribute to the social and cultural welfare of the surrounding community. The research approach used is qualitative with a case study type, where data is collected through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman interactive model, including data condensation, presentation, and conclusion. The study results indicate that the development of Fombrun's theory from the perspective of non-profit Islamic boarding school organizations produces the concept of “Panca Reputasi Pesantren”, which includes credibility, reliability, trustworthiness, responsibility, and local engagement elements. “Panca Reputasi Pesantren” integrates spiritual values with modern management strategies. This concept helps pesantren strengthen relationships with stakeholders and face competition with other educational institutions. This research has implications for expanding the concept of reputation in the context of non-profit organizations, primarily community-based religious institutions. It opens up space for further studies on spirituality-based reputation management.